Evaluation of In Vitro Culture Medium for Conservation of Chrysanthemum Varieties under Different Storage Environment - Lia Sanjaya; Budi Marwoto; Kurniawan Budiarto (Balai Besar Penelitian dan Pengembangan Bioteknologi dan Sumberdaya Genetik Pertanian, 2019)
In vitro technique for conservation of genetic resources of chrysanthemum was developed through the application of selected medium under different storage conditions. The research was conducted from June 2014 to October 2016. The experiment was conducted in a completely randomized design which consisted of three chrysanthemum varieties and seven medium formulations and maintained in two storage conditions, i.e. low-temperature and ambient room conditions. The results showed that plantlet of all varieties conserved under ½ MS + 6% sucrose had higher survivals and slighter death rates after 4, 7, and 9 months. Lowtemperature condition provided more suitable circumstances for the respected medium to preserve the plantlet life during 9 months of in vitro storage. Under these conditions, the plantlet survivals ranged 51.3–66.3%. While among the chrysanthemum varieties, Monalisa had highest plantlet survivals than Merahayani and Town Talk.